Identification of irreversible UF membrane foulants by fluorescence excitation–emission matrix coupled with parallel factor analysis. Issue 46 (1st October 2016) - Tian, Jiayu; Yu, Huarong; Shen, Yiwei; Shi, Wenxin; Liu, Dongmei; Gao, Shanshan; Cui, Fuyi
Abstract: In this work, a total of nine water samples were taken from different water sources at different seasons for UF membrane fouling experiments, with the purpose to find out if there were common foulant components responsible for the irreversible membrane fouling. It was found that the increase in DOC and UV254 in raw water caused a corresponding increase in the developing rate of irreversible membrane fouling, demonstrating NOM as the major membrane foulants. Using the fluorescence excitation–emission matrices coupled with parallel factor analysis, four fluorescence components in NOM were identified, i.e. microbial-derived and terrestrial-derived humic-like substances (C1 and C3), tryptophan-like and tyrosine-like proteins (C2 and C4). The C2 exhibited a strong correlation with the irreversible fouling of UF membrane, while no correlation between C4 and irreversible membrane fouling was observed. The humic-like substances were shown to be weakly correlated to the irreversible membrane fouling. By multivariate linear regression, synergistic fouling effect was identified between the C2 and C3, but a comparison of their coefficients revealed that C2 made a considerably larger contribution to the irreversible membrane fouling than C3. The results may provide insights into the development of appropriate fouling control strategies for sustainable UF operation.